Antibiotic Utilization Pattern in the Intensive Care Unit of Tertiary Hospital in West Java, Indonesia - Taradharani Wikantiananda; Adi Imam Tjahjadi; Reza Widianto Sudjud (Faculty of Medicine Universitas Padjadjaran, 2019)
Objective: To find out the pattern of antibiotic utilization in intensive care unit (ICU). The high use of antibiotics in intensive care may increase antibiotic resistance.Methods: This was a retrospective study with total sampling method from patients who were treated in ICU in the period of January to June 2016. Selected data is processed using the Anatomical Therapeutic Chemical (ATC) Classification/Defined Daily Dose (DDD) system as an international measurement standard for analyzing and comparing usage applied by the WHO.Results: The results showed that of the 57 medical records collected, the total antibiotic use was 295.72 DDD/100 bed-days. Levofloxacin, meropenem, ceftriaxone, ceftazidime, and metronidazole were the five maximally utilized antibiotics with 143.18, 49.88, 30.62, 19.74, dan 16.99 DDD/100 bed-days respectively.Conclusion: The most frequently used of antibiotics is ceftriaxone, used in 54.39% of patients. Whereas in number, the most widely used antibiotic is levofloxacin with a total of 143.18 DDD/100 bed-days.